Specially designed solar cells for hybrid photovoltaic-thermal generators - Mellor,AV; Guarracino,I; Llin,LF; Alonso,alvarez; Riverola,A; Thoms,S; Paul,DJ; Markides,C; Chemisana,D; Maier,S; Ekins-daukes,N (IEEE, 2016)
The performance of hybrid photovoltaic-thermal systems can be improved using PV cells that are specially designed to generate both electricity and useful heat with maximum efficiency. Present systems, however, use standard PV cells that are only optimized for electrical performance. In this work, we have developed two cell-level components that will improve the thermal efficiency of PV-T collectors, with minimal loss of electrical efficiency. These are a spectrally-selective low-emissivity coating to reduce radiative thermal losses, and a nanotextured rear reflector to improve absorption of the near-infrared part of the solar spectrum for heat generation.